The Impact of Corporate Governance on the adoption of Enterprise Risk Management at Institutions of Higher Education - ABUBAKR, AHMED ELTAHIR (2018)
Corporate governance has emerged during the last two decades as one of the main concerns in higher education sector. Researchers and practitioners perceive that maintaining best practice of corporate governance should result in a better institutional performance and subsequently bring back shareholders values benefits over a long term. Though the term “Corporate Governance” has been widely researched in public and private enterprises, little attention has been given to examine governance practices and structures in higher educational institutions (HEIs). On the other hand, the topic of “Enterprise Risk Management” has become vitally important during decades between scholars, institutions and politicians around the world. Scholars call for an integrated and interrelated process of examining, assessing and managing risks, uncertainties with a prospect of considering both negative and positive impacts on the organization’s projects, before, within and after their deployment. This research aims at contribute to the literature by providing empirical evidence of examining the internal and external factors for good governance and their impact on the successful adoption of Enterprise Risk Management at institutions of higher education in a local context of the UAE. The results of the study reveal that the variables “governance board process” and the “influence of regulatory authorities” have significant positive relationship with the successful adoption of enterprise risk management. The study also demonstrates that other governance variables identified in the study such as “governance board composition” and “expectations of stakeholders” don't have significant relationship with the successful adoption of enterprise risk management. The study calls for further qualitative studies to further investigate closely those factors.